A prospective clinical cohort study analyzing single‐unit implant crowns after three years of loading: introduction of a novel Functional Implant Prosthodontic Score (FIPS). Issue 10 (23rd August 2016) - Joda, Tim; Ferrari, Marco; Bragger, Urs
Abstract: Objectives: The aim of this prospective clinical cohort study was to validate implant crowns with a novel Functional Implant Prosthodontic Score (FIPS). Material and methods: Twenty patients were restored with cement‐retained crowns on soft tissue level implants (Institut Straumann AG, Basel, Switzerland) in posterior sites and annually followed‐up for 3 years. FIPS was applied for the objective outcome assessment including clinical and radiographic examinations. Five variables were defined for evaluation, resulting in a maximum score of 10 per implant restoration. The patients' level of satisfaction was recorded and correlated with FIPS. Results: All implants and connected crowns revealed survival rates of 100% without any biological or technical complications after three years of loading. The mean total FIPS score was 7.8 ± 1.5, ranging from 6 to 10. The variable "bone" revealed the highest scores (2 ± 0; range: 2–2), followed by "occlusion" (1.9 ± 0.1; range: 1–2). Mean scores for "design" (1.2 ± 0.6; range: 0–2), "mucosa" (1.3 ± 0.7; range: 0–2), and "interproximal" (1.4 ± 0.4; range: 1–2) were more challenging to satisfy. The patients expressed a high level of functional satisfaction (84.1 ± 9.5; range: 68–100). A significant correlation was found between FIPS and the subjective patients' perception with a coefficient of 0.88 ( P  < 0.0001). Conclusions: The findings of the clinical trial indicated the potential of FIPS as an objective and reliable instrument in assessing implant success. FIPS can be considered as a supportive tool to validate a satisfactory outcome as perceived by patients, to identify possible failure risks, and to compare follow‐up observations.